(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Patriotic education among students is an essential component of nurturing responsible citizenship and fostering a strong sense of national identity. It encompasses a range of principles and practices aimed at instilling love, pride, and loyalty towards one’s country while also promoting critical thinking, civic engagement, and respect for diversity. In this essay, we will explore the fundamentals of patriotic education and its significance in shaping the future of a nation.